Exergy loss analysis on heat transfer characteristics of twisted petaloid spirally wound tube with the convection boundary condition - Han, Yong; Li, Jia-ni; Zhang, Chong; Zhu, You-jian; Wu, Xue-hong; Lv, Cai; Zhang, Zhen-ya; Zhang, Can-can (Applied thermal engineering, 2023)
•Heat transfer characteristics of the twisted petaloid spiral wound tube (TPSWT) are investigated.•Expression of heat transfer exergy loss number (HTELN) is derived.•Characteristics of the HTELN is studied.•Correlation of the HTELN for the TPSWT is formulated. The spiral flow motivates an extra centrifugal force inducing the secondary flow to effectively enhance the heat transfer performance of spirally wound tubes (SWTs). In this research, the flow and heat transfer characteristics of twisted petaloid spirally wound tube (TPSWT) basis of exergy theory was numerically analyzed, which integrates the technologies of spiral coil, petaloid section and twisted channel. Firstly, the flow and heat transfer characteristics of the TPSWT are numerically investigated. Secondly, the heat transfer exergy loss number (HTELN, ζHT) is proposed. Furthermore, the relationship between η (heat transfer effectiveness) and ζHT is investigated. Finally, the correlations for Nupetal, η and ζHT in the form of classical power–law expression are calculated. The results show that, the secondary flow induced by the integration of the centrifugal force and the torsional force destroying the steady flow state, which enhances the heat transfer performance; ζHT can describe the heat transfer performance in 2 aspects, one is for the heat transfer irreversible loss, the other one is for the heat transfer efficiency; the predicted values of the regression functions are well aligned with the numerical calculated data (6.73% for Nupetal; 1.68% for η; 0.38% for ζHT).